PENGARUH FINANCIAL DISTRESS, GROWTH OPPORTUNITIES DAN LIQUIDITY TERHADAP KEPUTUSAN HEDGING PADA PERUSAHAAN PERTAMBANGAN BEI - Marhaenis, Luh Galang; Artini, Luh Gede Sri (E-Jurnal Manajemen; Vol 9 No 5 (2020)DO - 10.24843/EJMUNUD.2020.v09.i05.p07, 2020)
Efforts can be made to reduce the impact of business risks by implementing a hedging policy so as to reduce the impact caused by fluctuations in foreign exchange rates and protect the company's assets from risk exposure, namely mining companies. The purpose of this study is to explain the effect of financial distress, growth opportunities and liquidity on hedging decisions in mining companies. The sampling technique in this study used purposive sampling because in this study a sample of 32 companies from 48 populations of mining companies was obtained. Data analysis techniques used in this study used logistic regression. The results of data analysis show that financial distress has a negative and not significant effect on hedging decisions. Growth opportunities have a positive and significant effect on hedging decisions. Liquidity has a negative and significant effect on hedging decisions. Keywords: financial distress, growth opportunities, hedging, liquidity